Connective tissue graft and crown-resin composite restoration for the treatment of gingival recession associated with noncarious cervical lesions: Case series - Silveira, Camila Augusto [UNESP]; Mathias, Ingrid Fernandes [UNESP]; Neves, Felipe Lucas da Silva [UNESP]; dos Santos, Nídia Cristina Castro [UNESP]; Araújo, Cássia Fernandes [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Bresciani, Eduardo [UNESP]; Santamaria, Mauro Pedrine [UNESP] (Quintessence Publishing, 2017)
The purpose of this case series is to describe a restorative and surgical approach to treat the combined defect (CD)-gingival recession associated with noncarious cervical lesions (NCCL)-through connective tissue graft in combination with partial resin composite filling, restoring the crown zone plus 1 mm of the NCCL. A total of 10 patients were included. Bleeding on probing, probing depth, relative gingival recession, clinical attachment level, CD height, and dentin hypersensitivity were measured. The treatment provided statistically significant gain in clinical attachment level and shallow probing depths. The percentage of the combined defect coverage was 70% ± 20.2%. It can be concluded that this treatment protocol, in the presence of a partial resin composite restoration, can be used successfully to treat CD.